NAMPT Inhibition Induces Neuroblastoma Cell Death and Blocks Tumor Growth - Vallejo, Frederic A.; Sanchez, Anthony; Cuglievan, Branko; Walters, Winston M.; De Angulo, Guillermo; Vanni, Steven; Graham, Regina M. (Frontiers in Oncology, 2022)
High-risk neuroblastoma (NB) portends very poor prognoses in children. Targeting tumor metabolism has emerged as a novel therapeutic strategy. High levels of nicotinamide-adenine-dinucleotide (NAD+) are required for rapid cell proliferation. Nicotinamide phosphoribosyl transferase (NAMPT) is the rate-limiting enzyme for NAD+ salvage and is overexpressed in several cancers. Here, we determine the potential of NAMPT as a therapeutic target for NB treatment. NAMPT inhibition cytotoxicity was determined by trypan blue exclusion and LDH assays. Neuroblastoma stem cell self-renewal was evaluated by neurosphere assay. Protein expression was evaluated via Western blot. The effect of targeting NAMPT in vivo was determined using an NB1691-xenografted mouse model. Robust NAMPT expression was demonstrated in multiple N-MYC amplified, high-risk neuroblastoma cell lines. NAMPT inhibition with STF-118804 (STF) decreased ATP, induced apoptosis, and reduced NB stem cell neurosphere formation. STF treatment down-regulated N-MYC levels and abrogated AKT activation. AKT and glycolytic pathway inhibitors synergized with NAMPT inhibition inducing robust neuroblastoma cell death. Lastly, STF treatment blocked neuroblastoma tumor growth in mouse xenograft models. NAMPT is a valid therapeutic target as inhibition promoted neuroblastoma cell death in vitro and prevented tumor growth in vivo. Further investigation is warranted to establish this therapy’s role as an adjunctive modality.